Quantifying temporal trends in anthropogenic litter in a rocky intertidal habitat. (November 2020) - Weideman, Eleanor A.; Perold, Vonica; Omardien, Aaniyah; Smyth, Lucy K.; Ryan, Peter G.
Abstract: Most monitoring studies of marine anthropogenic debris have focused on sandy beaches, so little is known about litter on rocky shorelines. We surveyed litter trapped on a rocky intertidal shore in False Bay, South Africa, between May 2015 and March 2018. An exceptional upwelling of seabed litter occurred in November 2017 (70 items∙m −1 ). Excluding this event, monthly clean-ups at spring low tide collected 2 (1.3–3.1) items∙m −1 ∙month −1 and 31 (19.4–49.4) g∙m −1 ∙month −1 of which 74% was plastic (31% by mass). Litter loads peaked in autumn when seasonal rains washed litter into False Bay, suggesting that most litter comes from local land-based sources. Litter composition differed from that on a nearby sandy beach, with more glass and other dense items on the rocky shore, but 60% of plastic items floated in water. Sand inundation and biotic interactions helped to trap buoyant plastics in the intertidal zone. Highlights: One of few studies to monitor litter trapped on a rocky intertidal shore Plastics made up 74% of litter by count but only 31% by mass. Most plastic was disposable flexible packaging (bags and food packaging). Litter loads 1–2 orders of magnitude higher than average during an upwelling event. Rocky shore trapped more bags/packets, but less rigid plastics, than nearby sandy beach.